Determinants of Mortality in Russian Regions: an Empirical Analysis - Tatiana Blinova; Svetlana Bylina (European Regional Science Association (ERSA), 2012)
The objective of this paper is to make an empirical analysis and econometric evaluation of determinants of mortality for population of the able-bodied age in Russian regions. The model that was evaluated included five groups of factors (economic, social, ecological, demographic and behavioral). Results of the empirical analysis are presented to show that statistically relevant indicators are the characteristics of the region, way of life of the people and investments in the health care. Taxonomy of the regions of the Russian Federation is made according to basic classes of causes of death of the population of the able-bodied age that is developed by employing hierarchical cluster analysis and the SPSS statistical processing software. The results of the study show that the regional structure of mortality among the population of the able-bodied age is governed by specific characteristics of the region. The relationship between the ecological adversity and high mortality from neoplasm is revealed. The hypothesis that anti-social behavior affects the level of mortality from external causes is confirmed. It is argued that increased investments in the public health service and promotion of the healthy way of life can help reduce the mortality among the able-bodied population from cardiovascular diseases. The regression equations are evaluated by using the data openly presented by the Federal State Statistics Service on the website of Rosstat. The study of the nosological profile of mortality among the able-bodied population by Russian regions allowed identify the territorial features of the structure of causes of death, which can be used when developing regional strategies for reducing mortality among the population of the able-bodied age.
Keywords: 330